PPM PENGELOLAHAN DAN PEMBINAAN USAHA MIKRO PEMBUATAN KRUPUK MUJAIR DAN BELUT DI DUKUH KAUMAN SUMBER REJO SURABAYA BARAT - Kartika, Chandra; Rudiatno, Rudiatno; Suhariningsih, Lilik; Riduwan, Riduwan; Qosim, Nanang (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
This Community Empowerment Program activity is carried out in order to provide more assistance and provide community empowerment that has been done by partners, namely Mrs. Hj. Asmaul Husna in Sumber Rejo II Rt. 3 Rw 2 Pakal Subdistrict, Benowo Surabaya located no more than 4.1 kilometers from Wijaya Putra University. Krupuk community partnership program partner in Sumber Rejo II Village Rt. 3 Rw 2 Pakal Subdistrict, Surabaya located no more than 4.5 kilometers from Wijaya Putra University, using the surrounding residents as employees and production personnel. The purpose of this Community Empowerment Program activity is to develop SME partners production krupuk Ikan with the target to be achieved is SMEs has capital in the form of a krupuk dryer oven machine to increase production, good business management, expand the market reach, have product design, have a krupuk packaging machine and halal label krupuk products, so that SMEs have the ability to be a business that is ready to meet customer demand and ready to be competent. The methods implemented in this Community Empowerment Program are training and mentoring: training on how to use a krupuk dryer oven machine, packaging machine, business management assistance so that partners become resilient and competitive SMEs. In addition, the manufacture of TTG and adequate production equipment is also carried out in this activity. Training and mentoring activities of business management carried out by including marketing management (potential market identification, promotion, selection of sales locations, entrepreneurship (innovation of krupuk production variations), financial administration (determination of production costs and preparation of simple financial statements) and quality and health management (improvement of production design, testing to obtain halal production label certification). The result of this Community Empowerment Program is expected to increase the income and productivity of the target partner group